Knowledge, attitudes and perceptions of correctional officers towards inmates with HIV/AIDS - Ncoyo, Kholekile Dennis (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2012.